2015
DOI: 10.1111/plb.12355
|View full text |Cite
|
Sign up to set email alerts
|

Diel trends in stomatal response to ozone and water deficit: a unique relationship of midday values to growth and allometry in Pima cotton?

Abstract: Plant responses to ozone (O3 ) and water deficit (WD) are commonly observed, although less is known about their interaction. Stomatal conductance (gs ) is both an impact of these stressors and a protective response to them. Stomatal closure reduces inward flux of O3 and outward flux of water. Stomatal measurements are generally obtained at midday when gas exchange is maximal, but these may not be adequate surrogates for stomatal responses observed at other times of day, nor for non-stomatal responses. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 95 publications
(193 reference statements)
2
12
0
Order By: Relevance
“…The eO 3 limited the growth of aboveground organs of soybean, but no changes in root growth and root/shoot ratio were found due to the similar decreases in shoot and root dry biomass, consistent with previous study on soybean (Morgan et al 2003, Hewitt et al 2016. Besides its influence on biomass accumulation, eO 3 caused an increase in height growth at the expense of diameter growth (Table 1), consistent with the findings that O 3 alters plant allometry towards slender stem shapes (Pretzsch et al 2010, Grantz et al 2016. Increased specific leaf area, whole-plant leaf-area to biomass ratio and whole-plant leaf-area to root biomass ratio would increase carbon acquisition at the cost of higher transpiring surface per unit of carbon fixation (Poorter 1999, Brunner et al 2015.…”
Section: Ozone Impacts On Growth and Biomass Allocationsupporting
confidence: 90%
See 1 more Smart Citation
“…The eO 3 limited the growth of aboveground organs of soybean, but no changes in root growth and root/shoot ratio were found due to the similar decreases in shoot and root dry biomass, consistent with previous study on soybean (Morgan et al 2003, Hewitt et al 2016. Besides its influence on biomass accumulation, eO 3 caused an increase in height growth at the expense of diameter growth (Table 1), consistent with the findings that O 3 alters plant allometry towards slender stem shapes (Pretzsch et al 2010, Grantz et al 2016. Increased specific leaf area, whole-plant leaf-area to biomass ratio and whole-plant leaf-area to root biomass ratio would increase carbon acquisition at the cost of higher transpiring surface per unit of carbon fixation (Poorter 1999, Brunner et al 2015.…”
Section: Ozone Impacts On Growth and Biomass Allocationsupporting
confidence: 90%
“…The enhanced whole‐plant height to biomass ratio (HMR) and total leaf area/root biomass imply that eO 3 also restricts the uptake capacity of root for higher transpiring leaf surface of soybean plants (Sultan , Oikawa and Ainsworth ). These altered growth patterns would have important consequences for plant hydraulic properties and plant water relations, which can potentially affect the growth and survival of O 3 ‐sensitive species under O 3 pollution and changing climate in the future (Grantz , Wilkinson and Davies , Grantz et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In droughted Pima cotton ( Gossypium barbadense L.) exposed to elevated O 3 , the relative reduction in stomatal conductance was half that of well‐watered plants with elevated O 3 and 20% that of well‐watered plants grown in low O 3 in early to mid‐morning (Grantz et al . (). Production in Pima cotton was correlated with early morning, not midday assimilation.…”
Section: Organismal Effects Cascade To Community and Ecological Procementioning
confidence: 97%
“…; Grantz et al . ). The complexity of the physiological basis of ozone tolerance is considered in soybean genotypes differing in ozone tolerance (Chutteang et al .…”
mentioning
confidence: 97%
“…It is suggested that the integration of responses to multiple stresses may not be synergistic, as is often assumed (see Visser et al 2016), and that responses to specific stresses, such as drought and salinity, may be linked through metabolomics, and distinguished from responses to other stresses, such as high temperature (Sun et al 2016). A number of studies investigate the interaction of ozone with specific aspects of changing climate, emphasising impacts on photosynthesis, plant water relations and antioxidant metabolism in tree and crop species (Fusaro et al 2016;Grantz et al 2016). The complexity of the physiological basis of ozone tolerance is considered in soybean genotypes differing in ozone tolerance (Chutteang et al 2016).…”
mentioning
confidence: 99%